Technological Innovation, Commercialization, and Regional Development: Computer Graphics in Utah, 1965-1978. - Lehning, James R. (Information & Culture, 2016)
The Computer Science Program at the University of Utah, founded in 1965 with support from the Department of Defense, was a significant contributor to the development of computer graphics technology in the following decade and thereafter. In 1968 a spin-off company, Evans & Sutherland Computer Corporation, was established to manufacture and market this technology. The practices of innovation drawn from the Department of Defense, the research and instructional programs of the Computer Science Program, and Evans & Sutherland's marketing of graphics products interacted to turn the Salt Lake Valley into an important center of computer innovation and manufacturing.